AI-DRIVEN EDUCATIONAL INTERVENTIONS: HARNESSING ARTIFICIAL INTELLIGENT TO FOSTER LIFELONG LEARNING (A SYSTEMATIC INVESTIGATION) - Liando, Nihta V. F.; Tatipang, Devilito Prasetyo; Budiman, Jeihn N. C.; Ganap, Nindy N.; Lengkoan, Fergina (Lingua Scientia, 2025)
This systematic investigation delves into the integration of artificial intelligence (AI) into educational interventions with the aim of fostering lifelong learning. The study examines the efficacy of AI-driven educational interventions, addressing key challenges and ethical considerations associated with their implementation, and proposing mitigation strategies. Drawing insights from a systematic review, the research highlights the transformative potential of AI technologies in promoting lifelong learning outcomes, including increased learner engagement, enhanced knowledge retention, and improved skill acquisition. However, the investigation also uncovers challenges such as disparities in access to AI-powered learning tools, algorithmic bias and discrimination, concerns about data privacy and security, and the potential depersonalization of education. Mitigation strategies are proposed to address these challenges, including investing in infrastructure and resources for equitable access, implementing transparent data collection and reporting practices, and fostering a human-centered approach to AI in education. By prioritizing ethical principles and values, stakeholders can harness the benefits of AI-driven educational interventions while safeguarding learners' privacy, autonomy, and well-being. The findings of this investigation contribute to the ongoing discourse on the responsible integration of AI into lifelong learning frameworks, providing insights and recommendations for educators, policymakers, and technology developers striving to create inclusive and equitable learning environments in the digital age.